Hikmah Peristiwa Isra' Mi'raj sebagai Model Pendidikan Karakter Islami bagi Generasi Z di Era Digital - Amsal Qori Dalimunthe (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Islamic character education is an important element in forming a morally and spiritually strong Generation Z in the digital era. This article aims to analyze the application of wisdom values from the Isra' Mi'raj event in building Generation Z's Islamic character through digital media. The focus of the research includes three main values, namely solid faith, moral and spiritual values, and historical values, each of which has a foundation in the Qur'an and Islamic teachings. This research uses the literature study method by analyzing literature from national and international journals, books, and scientific articles. The data were analyzed interpretatively to identify the relevance of integrating Islamic values with digital technology in character education. The results showed that despite the challenges of low digital literacy among educators and exposure to negative content, great opportunities exist through the utilization of social media, interactive applications, and technologies such as augmented reality. The integration of traditional values and digital technology is an effective strategy to build Generation Z Islamic character that is relevant to the challenges of the times and still based on Islamic teachings.